A Review of Cognitive Approaches in SLA: Identifying the Most Influential Factors from Key Studies - Rahman, Erwan; Norahmi, Maida; Pratika, Dellis; Fauziyah, Rahima Annisa; Joyanaku, Zico Oktavino (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
This study investigates cognitive approaches to Second Language Acquisition (SLA) by examining key components: attention, working memory, L1 transfer, and cognitive restructuring. Despite extensive research on individual cognitive factors in SLA, there remains a critical gap in understanding how these elements interact systemically in multilingual contexts, particularly in Indonesian EFL classrooms where traditional teaching methods often neglect cognitive principles. This study aims to develop an integrated cognitive model of SLA and propose practical pedagogical strategies tailored to Indonesia’s unique multilingual environment. A systematic review is conducted using the SALSA framework (Search, Appraisal, Synthesis, and Analysis), incorporating NVivo 12-assisted thematic analysis of ten peer-reviewed studies published between 2018 and 2023. The methodology follows PRISMA 2020 guidelines for transparent study selection and applies qualitative analysis to identify patterns across diverse cognitive studies. The findings reveal that attention serves as a gateway for input processing and learning, while working memory determines learners’ capacity to handle linguistic information. Additionally, L1 transfer either facilitates or hinders L2 learning depending on language distance and learner awareness. Cognitive restructuring enables proceduralization of explicit knowledge. In the Indonesian EFL context, these mechanisms are especially relevant. This study suggests cognitively informed instruction to enhance learning outcomes.